INFLUENCE OF E-LEARNING ON THE DEVELOPMENT OF THE COUNTRY - Osmolyk, Kateryna (Електронне наукове фахове видання “ВІДКРИТЕ ОСВІТНЄ Е-СЕРЕДОВИЩЕ СУЧАСНОГО УНІВЕРСИТЕТУ”, 2017)
With development of information and communication technologies in the world appears the question of changes in education system, the question of changes in the system of training, and retraining of competitive and highly skilled specialists for the modern labor market. One of the most promising and developing forms of modern training is the technology of e-learning. Each specialist and master affects not only his own financial life, but also the development of the whole country. That is why the problem of the impact of the development of IC technologies, in particular e-learning on the development of the country, is relevant. DOI: https://doi.org/10.28925/2414-0325.2017.3.105dv9